A Numerical Study of Characteristic Slow-Transient Behavior of a Compressible 2D Gas-Liquid Two-Fluid Model (Advances in Applied Mathematics and Mechanics, 2018)
The purpose of this paper is to gain some insight into the characteristicbehavior of a general compressible two-fluid gas-liquid model in 2D by using numericalcomputations. Main focus is on mass transport phenomena. Relatively fewnumerical results in higher dimensions can be found in the literature for this two-fluid model, in particular, for cases where mass transport dynamics are essential.We focus on natural extensions to 2D of known 1D benchmark test cases, like waterfaucet and gas-liquid separation, previously employed by many researchers for thepurpose of testing various numerical schemes. For the numerical investigations,the WIMF discretization method introduced in [SIAM J. Sci. Comput. 26 (2005),1449] is applied, in combination with a standard dimensional splitting approach.Highly complicated flow patterns are observed reflecting the balance between accelerationforces, gravity, interfacial forces, and pressure gradients. An essentialingredient in these results is the appearance of single-phase regions in combinationwith mixture regions (dispersed flow). Solutions are calculated and shown fromearly times until a steady state is reached. Grid refinement studies are included todemonstrate that the obtained solutions are not grid-sensitive.